2010
DOI: 10.1108/30743581080001333
|View full text |Cite
|
Sign up to set email alerts
|

Performance of debt free firms

Abstract: This paper compares the performance of portfolios of debt free firms to comparable portfolios of leveraged firms. The results of the study indicate that investments in portfolios of debt free firms tend to generate higher returns than investments in their peer portfolios of leveraged firms over long and short periods. The results have clear implications for investment decisions and investment performance. Investors tend to reward firms that resist the urge to borrow heavily and operate with debt free balance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
(4 reference statements)
2
11
1
Order By: Relevance
“…Financial leverage presents a significant negative effect (at the 1% level) on stock exchange performance, confirming expectations that increasing the indebtedness degree of the company would bring down its value in the view of investors. This result confirms the findings of previous studies (Korteweg, 2004, Zaher, 2010, which found that investments made in companies with low financial leverage give higher returns to investors.…”
Section: Processing the Model To Correct The Effects Of Serial Correlsupporting
confidence: 92%
“…Financial leverage presents a significant negative effect (at the 1% level) on stock exchange performance, confirming expectations that increasing the indebtedness degree of the company would bring down its value in the view of investors. This result confirms the findings of previous studies (Korteweg, 2004, Zaher, 2010, which found that investments made in companies with low financial leverage give higher returns to investors.…”
Section: Processing the Model To Correct The Effects Of Serial Correlsupporting
confidence: 92%
“…The findings in this study support those of Dimitrov and Jain (2006), Korteweg (2004), Penman et al (2007). Zaher (2010), who provided evidence that that there is a negative relationship between leverage and stock returns, contradicts the study by Bhandari (1988), who argues that stock returns increase with leverage.…”
Section: Resultscontrasting
confidence: 52%
“…Bhandari (1988) [4] studied the effect of total common equity, beta and debt equity ratio on the average returns generated by the stocks. Zaher (2009) [10] has studied the performance of debt free firms specifically. This paper compares the equity performances of leveraged and zero debt firms.…”
Section: Introductionmentioning
confidence: 99%
“…But there is a negative side too to the debt story. It involves outflow of cash at regular intervals which may stifle the net flow of cash (Zaher 2009) [10]. Both, being a zero debt firm or a leveraged firm have their own sets of pros and cons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation